2007
DOI: 10.1002/jor.20462
|View full text |Cite
|
Sign up to set email alerts
|

In vivo mechanical condition plays an important role for appearance of cartilage tissue in ES cell transplanted joint

Abstract: The objective of this study was to evaluate the effects of the mechanical environment on the formation of cartilage tissue in transplanted embryonic stem (ES) cells. Full-thickness osteochondral defects were created on the patella groove of SD rats, and ES cells (CCE ES cells obtained from 129/Sv/Ev mice and Green ES FM260 ES cells obtained from 129SV [D3] -Tg [NCAG-EGFP] CZ-001-FM260Osb mice) were transplanted into the defects embedded in collagen gel. The animals were randomly divided into either the joint-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 23 publications
(25 reference statements)
2
40
0
Order By: Relevance
“…[12][13][14][15] Recent studies have reported that repetitive compression forces enhance chondrogenic differentiation. [35][36][37] Therefore, we have proposed a hypothesis that a combination of compression forces during weight bearing and the elastic modulus of the DN gel implanted at the bottom of the cartilage defect may provide the cells that filled the defect with an appropriate physical environment to induce chondrogenic differentiation. We are currently conducting a study to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Recent studies have reported that repetitive compression forces enhance chondrogenic differentiation. [35][36][37] Therefore, we have proposed a hypothesis that a combination of compression forces during weight bearing and the elastic modulus of the DN gel implanted at the bottom of the cartilage defect may provide the cells that filled the defect with an appropriate physical environment to induce chondrogenic differentiation. We are currently conducting a study to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…40 With regard to the repair of cartilage lesions, joint movement enhances the healing of defects in the articular cartilage. [41][42][43] Thus, primary pain relief may occur as the result of enhanced homeostatic capacity through improved blood flow and increased mechanical stimuli. The reduction of primary pain may lead to a decrease in secondary myogenic pain.…”
Section: Fig 2 Long-term Effect (5 Participants)mentioning
confidence: 99%
“…In one group, free motion of the knee joint was allowed, whereas in the second group the knee joints were immobilized, due to which the patella did not fully cover the defect. Tumors were formed in all the immobilized knee joints, whereas fibrocartilage was amongst the regenerated tissue when knee movement was allowed [164]. The confined space outside the defect created by the movement of the patella, might prevent tumor growth, as also suggested when subcutaneous and knee joint tumors in mice were compared [162].…”
Section: Tumorigenicity Of Escsmentioning
confidence: 94%
“…Studies describing the injection of undifferentiated ESCs into the joints of mice and rats have used samples of 10-15 µl with a cell density of 10 million cells/ml [162][163][164]. Even though we will implant differentiated cells, the high cell numbers required to create a cartilage implant will increase the chance of introducing remaining undifferentiated cells into the knee.…”
Section: Teratoma Formationmentioning
confidence: 99%
See 1 more Smart Citation